DAMPAK PELATIHAN DAN PENGEMBANGAN TERHADAP MANAJEMEN KINERJA GURU DI SEKTOR PENDIDIKAN - Elna Sari Nasution; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the impact of training and development on teacher performance in the education sector, focusing on the implementation of effective performance management. The research method used is descriptive qualitative. The results of the study indicate that the implementation of good performance management contributes significantly to improving teacher performance, work motivation, and teacher satisfaction. In addition, there is a positive relationship between the quality of teacher teaching and student learning outcomes. Improved communication and cooperation between teachers are also observed, creating a collaborative culture that supports professional development. This study concludes that investment in teacher training and development is essential to improving the overall quality of education. Recommendations are given to strengthen the performance of the management system in order to achieve better education goals in the future.